On Solarity: Six Principles for Energy and Society After Oil - Szeman, Imre (Stasis, 2020)
This essay critically interrogates the hopes, fears, and fantasies that accompany the future social and political projections of a transition to solar energy. It does so through the elaboration of six principles for understanding solar energy, with the aim of adding context and complexity to the principle energy narrative already emerging around this source of energy. Solar contains a double promise: energy without fuel and infinite energy. But despite the radical possibilities that might emerge from this fundamental redefinition of our relation to energy, solar also contains all manner of limitations—the weight of the materials necessary to create solar power; the blunt reality of existing forms of economics and politics that work to contain the changes solar might bring into existence; and the mechanisms of power that are likely to contain solar within (in Bataille’s term) a restrictive economy. Against the techno-determinist tendency to imagine that the introduction of solar energy will produce radical social change on its own, I argue for the need to articulate and struggle for “solarity,” a politics appropriate to the coming challenges of the solar era.